Full assignment of the 1H NMR spectrum of heteroleptic polyazaaromatic Ru(II) complexes based on long‐range interligand NOEs. (11th February 2013) - Mugeniwabagara, Epiphanie; Fusaro, Luca; Luhmer, Michel
<x xml:space="preserve">Abstract</x> Chemical equivalence in symmetrical polyazaaromatic ligands is not necessarily retained in the corresponding heteroleptic ruthenium(II) complexes, and the assignment of the 1H NMR spectrum of these octahedral metallic compounds is therefore not straightforward. This work shows that full assignment can be achieved on the basis of long‐range interligand NOE measurements. Copyright © 2013 John Wiley & Sons, Ltd.